The Effect of Organizational Citizenship Behavior (OCB) and Work-Life Balance (WLB) on Employee Performance at PT. Singosari 23 - Zalzela, Azalia Rahma; Mardiana, Nova; Andriani, Lis (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
PT. Singosari 23 is a company engaged in the food and beverage sector that has carried the concept of the current generation in Bandar Lampung since August 2020. This company has an organizational culture that adheres to a sense of kinship, where employees are accustomed to working together collaboratively so that they are involved in the company and an organizational existence is formed. citizenship behavior. Implementation of organizational citizenship behavior in companies can improve employee performance and company effectiveness. In addition, work-life balance also has an important role in employee performance in reducing work-related stress. The purpose of this study is to determine the effect of organizational citizenship behavior and work-life balance on employee performance at PT. Singosari 23. The research method used is quantitative, with data collection methods using questionnaires distributed to all employees of PT. Singosari 23 as many as 154 people. The scale of measurement in this study uses a Likert scale. The analysis used is a simple linear regression test using IBM SPSS version 26. The results of this study indicate that the first hypothesis is supported, namely, organizational citizenship behavior affects employee performance, while the second hypothesis is not supported, namely work-life balance does not affect employee performance. Suggestions for the company PT. Singosari 23 is that employees should have more tolerance towards the company, and employees can separate personal and office matters and increase their loyalty to the company.